Unfolded protein response is activated in Lewy body dementias. (17th August 2015) - Baek, Jean‐Ha; Whitfield, David; Howlett, David; Francis, Paul; Bereczki, Erika; Ballard, Clive; Hortobágyi, Tibor; Attems, Johannes; Aarsland, Dag
Abstract : Aim: The unfolded protein response (UPR) is a pro‐survival defence mechanism induced during periods of endoplasmic reticulum stress, and it has recently emerged as an attractive therapeutic target across a number of neurodegenerative conditions, but has not yet been studied in synuclein disorders. Methods: The level of a key mediator of the UPR pathway, glucose‐regulated protein 78 (GRP78), also known as binding immunoglobulin protein (BiP), was measured in post mortem brain tissue of patients with dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD) in comparison with Alzheimer's disease (AD) and age‐matched controls using Western blot. The UPR activation was further confirmed by immunohistochemical detection of GRP78/BiP and phosphorylated protein kinase RNA‐like endoplasmic reticulum (ER) kinase (p‐PERK). Results: GRP78/BiP was increased to a greater extent in DLB and PDD patients compared with AD and control subjects in cingulate gyrus and parietal cortex. However, there were no changes in the prefrontal and temporal cortices. There was a significant positive correlation between GRP78/BiP level and α‐synuclein pathology in the cingulate gyrus, while AD‐type pathology showed an inverse correlation relationship in the parietal cortex. Conclusion: Overall, these results give emphasis to the role of UPR in Lewy body dementias, and suggest that Lewy body degeneration, in combination with AD‐type pathologies, is associated with increased UPR activation to a greater extent than AD alone, possibly as a consequence of the increasing load of ER proteins. This work also highlights a novel opportunity to explore the UPR as a therapeutic target in synuclein diseases. Abstract : The unfolded protein response (UPR) has been proposed as a therapeutic target in a number of neurodegenerative diseases. In this paper it is shown that the UPR appears to play a role in Lewy body disorders, highlighting a possible target for intervention in this group of diseases.